Acute Pancreatitis Complicated with Combined Copper Sulphate and Kerosene Poisoning A Case Report - Amin, Md Robed; Anonnya, Kaniz Fatema; Khosru, Md Omar; Manik, Abul Hayat; Mohammad, Raquib Hasan (Bangladesh Journal of Medicine, 2015)
Abstract not available Bangladesh J Medicine Jul 2015; 26 (2) : 79-82